Upaya Promotif Preventif Kesehatan Gigi melalui Penyuluhan dan Sikat Gigi Massal - Sultan Amin Yasin; Utari Zulkaidah; Yulistina Yulistina; Arsad Arsad; Nofyanto Tanjung Bulu; Ibrahim Ibrahim (Universitas Pahlawan Tuanku Tambusai, 2026)
Oral and dental health is an important part of overall health, especially in early childhood. Lack of knowledge about proper oral hygiene practices can increase the risk of dental caries among children. This community service activity aimed to improve children's knowledge and skills in maintaining oral hygiene through dental health education and mass tooth brushing activities. The program was conducted at Taman Bermain Aisyiyah in Kamirie Hamlet, Mattiro Tasi Village, targeting early childhood students. The methods used included dental health counseling, demonstration of proper tooth brushing techniques, and mass tooth brushing practice guided by lecturers and students. The results showed that the children were enthusiastic in participating in the activities and were able to practice proper tooth brushing techniques after the demonstration. This activity contributed to improving children's awareness and habits in maintaining oral and dental health from an early age.